Evaluation of Intensive Care Units Nurses' Knowledge regarding Ventilator Associated Pneumonia Prevention in Al-Nasiriya City. - Shinjar, Fatima; A. Khasal, Qasim (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
A form of lung infection known as ventilator-associated pneumonia affects patients in hospitals who are on mechanical ventilators. Usually, it influences the cause of rising rates of disease and mortality. Hospital stays for patients with ventilator-acquired pneumonia are longer, and their mortality rate might reach 20–30%. The purpose of the present study was to evaluate the nurses' knowledge concerning preventing of ventilator-associated pneumonia in the intensive care units of Al-Nasiriya City hospitals. Descriptive study was conducted through the present investigation from 31st March, 2020 to 30th of September, 2020. Eighty nurses chosen purposive from intensive care units at AL-Hussein Teaching hospital and Al-Nasiriyah Heart Center. Including (44) females and (36) males. To measure the variables, the researcher constructed a questionnaire. The questionnaire was divided into two sections: demographic information as well as nurses' knowledge about how to prevent ventilator-associated pneumonia. A panel of specialists determined the validity. The data analyzed through descriptive and inferential statistics. The majority of the participants were having poor knowledge about prevention of ventilator associated pneumonia. Non-significant correlation between socio-demographic variables (age, gender, marital status, qualification of nurses, working shift, years of experience in ICU as well as working place) and nurses' Knowledge regarding prevention of ventilator associated pneumonia. New nurses working in ICU should participate in a training program to increase their knowledge of how to prevent ventilator-associated pneumonia. Periodically evaluating as well as for training ICU nurses to increase their understanding of evidence-based practices and nursing interventions for ventilator-associated pneumonia prevention.